A Healthy Dental Nutrition Card as A Parenting Pattern to Prevent Stunting in Toddlers - Junaidi, Junaidi; Nurmawi, Yesi; Surayah, Surayah; Estuti, Wiwit (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: The healthy teeth nutrition card (Kartu Nutrisi Gigi Sehat) is a development model for parenting patterns to prevent stunting in toddlers. These cards were developed for young children and are efficient for children and health practitioners to carry and play with. It is hoped that parenting patterns in the form of healthy dental nutrition can prevent caries which affects food intake and nutritional status. The aim of the research is to develop a healthy dental nutrition card as a parenting pattern to prevent stunting in toddlers. Method: This research is Research and Development (R&D), carried out at Posyandu Widuri VI, Paal Lima Village, Jambi City. Media and material validation involved 6 experts. The research subjects were 16 toddlers, 4 cadres, 4 community health center staff, 2 PKK people, and 16 mothers of toddlers. The data collected using questionnaires. Results: Healthy dental nutrition cards are very eligible for use to promote dental health as a parenting pattern to prevent stunting in toddlers. Conclusion: It is recommended that future research test the effectiveness of healthy dental nutrition cards